A letter to three witches - Bass, Elizabeth, 1965- (Kensington Publishing Corp., 2022)
"Nearly a century ago, Gwen Engel's great-great-grandfather cast a spell with catastrophic side-effects. As a result, the Grand Council of Witches forbade his descendants from practicing witchcraft...Yet magic may still be alive...Gwen and her cousins, Trudy and Milo, receive a letter from Gwen's adopted sister, Tannith, informing them that she's bewitched one of their partners and will run away with him at the end of the week. While Gwen...[is] worried that local grad student Jeremy is secretly a Watcher doing his own research"--